2006
DOI: 10.1159/000092779
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Bell’s Palsy in Athens, Greece – A Hospital-Based Retrospective Evaluation over Fifteen Years

Abstract: Epidemiological data on the incidence of Bell’s palsy (BP) are conflicting. The aim of this retrospective study was to evaluate the variation of cases of BP acutely presented in the emergency room of our department over a 15-year period (January 1990 to December 2004). We examined the monthly and seasonal distribution of BPs among 36,312 patients who came to our emergency services and compared it with the assumed equal distribution of cases over the year (null hypothesis) using χ2 techniques. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
17
1
1
Order By: Relevance
“…Findings of previous studies with regard to the seasonality of BP are inconsistent. Some studies have suggested that the cold season is associated with a higher occurrence of BP [5,17,22,23], while others have not observed any seasonal variations [1,12,24]. None of those earlier studies evaluated the seasonality of BP in as large a study as the one used here.…”
Section: Discussionmentioning
confidence: 80%
“…Findings of previous studies with regard to the seasonality of BP are inconsistent. Some studies have suggested that the cold season is associated with a higher occurrence of BP [5,17,22,23], while others have not observed any seasonal variations [1,12,24]. None of those earlier studies evaluated the seasonality of BP in as large a study as the one used here.…”
Section: Discussionmentioning
confidence: 80%
“…Although it has been researched over time, the true cause was still unclear [8,9]. Spengos et al [10] has reported that greatest incidence of BP has been observed among the Japanese and the Mexican population, while the least incidence was among the Swedish population. There have been some previous studies about the seasonal incidence of BP.…”
Section: Discussionmentioning
confidence: 99%
“…O mesmo verificou-se no estudo de Yanagihara [6], em que a incidência máxima ocorreu entre a segunda e a quarta décadas de vida. Sazonalmente, Spengos et al [7] obtiveram resultados semelhantes aos do presente estudo, com um declínio da paralisia de Bell no verão e um pico de incidência no inverno.…”
Section: Discussionunclassified